Impact of the COVID-19 Pandemic on Radiology in Inpatient and Outpatient Care in Germany: A Nationwide Survey Regarding the First and Second Wave - Bernatz, Simon; Afat, Saif; Othman, Ahmed E.; Nikolaou, Konstantin; Sieren, Malte; Sähn, Marwin-Jonathan; Pinto dos Santos, Daniel; Penzkofer, Tobias; Bucher, Andreas Michael; Hamm, Bernd; Vogl, Thomas J.; Bodelle, Boris; RACOON Consortium; Gussew, Alexander; König, Alexander; Surov, Alexey; Bucher, Andreas; Mahnken, Andreas; Bücker, Arno; Hamm, Bernd; Valentin, Birte; Stroszczynski, Christian; Kuhl, Christiane; Düber, Christoph; Kloth, Christopher; Kütting, Daniel; Maintz, David; Kotter, Elmar; Bohrer, Evelyn; Bamberg, Fabian; Güttler, Felix; Meinel, Felix; Schwarz, Florian; Wacker, Frank; Kostka, Frederik; Krombach, Gabriele; Antoch, Gerald; Adam, Gerhard; Borte, Gudrun; Kauczor, Hans-Ulrich; Winther, Hinrich; Kleesiek, Jens; Ricke, Jens; Kühn, Jens-Peter; Lotz, Joachim; Barkhausen, Jörg; Peldschus, Kersten; Nikolaou, Konstantin; Pech, Maciej; Sieren, Malte; Weber, Marc-André; Both, Marcus; Makowski, Marcus; Fink, Matthias; Frölich, Matthias; May, Matthias; Beer, Meinrad; Forsting, Michael; Ingrisch, Michael; Uder, Michael; Hosten, Norbert; Hamer, Okka; Jansen, Olav; Isfort, Peter; Kuhl, Philipp Josef; Hoffmann, Ralf-Thorsten; Braren, Rickmer; Rischen, Robert; Klöckner, Roman; Ahmed, Saheeb; Afat, Saif; Pätzholz, Simon; Schönberg, Stefan; Kröncke, Thomas; Vogl, Thomas; Bley, Thorsten; Persigehl, Thorsten; Denecke, Timm; Penzkofer, Tobias; Teichgräber, Ulf; Attenberger, Ulrike; Nicolas, Volkmar; Heindel, Walter; Wohlgemuth, Walter (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Objectives To find out the opinion of radiological inpatient and outpatient medical staff regarding the measures taken in relation to the COVID-19 pandemic during the first and second waves and to identify the measures that are still perceived as needing improvement.Materials and Methods We conducted an anonymous online survey among more than 10 000 radiologists/technicians in Germany from January 5 to January 31, 2021. A total of 862 responses (head physicians, n = 225 [inpatient doctors, n = 138; outpatient doctors, n = 84; N/A, n = 3]; radiologic personnel, n = 637 [inpatient doctor, n = 303; outpatient doctor, n = 50; inpatient technician, n = 217; outpatient technician, n = 26; N/A, n = 41]) were received. Questions of approximation, yes/no questions, and Likert scales were used.Results During the first/second wave, 70 % (86/123)/43 % (45/104) of inpatient and 26 % (17/66)/10 % (5/52) of outpatient head physicians agreed that they received financial support from the authorities but the majority rated the financial support as insufficient. During the first and second wave, 33 % (8/24) and 80 % (16/20) of outpatient technicians agreed that they were adequately provided with personal protective equipment. The perceived lack of personal protective equipment improved for all participants during the second wave. Inpatient [outpatient] technicians perceived an increased workload in the first and second wave: 72 % (142/198) [79 % (19/24)] and 84 % (146/174) [80 % (16/20)]. Conclusion: Technicians seem increasingly negatively affected by the COVID-19 pandemic in Germany. Financial support by the competent authorities seems to be in need of improvement.Key Points: Citation Format
Keywords: COVID-19; SARS-CoV-2; outpatients; inpatients; surveys and questionnaires